ILLEGAL DRUG TRAFFICKING AS A SOCIAL PROBLEM - MUSAEV , Djamaliddin (Тараққиёт тадқиқотлари: илмий-амалий анжуманлар материаллари тўплами, 2025)
Distribution and trafficking of drugs as a social phenomenon People of different cultures have been using drugs for several thousand years. Many of the substances that have become the subject of illegal business in our time have been used for thousands of years for various purposes: for example, during religious ceremonies, to restore strength, to relieve pain and discomfort, mental suffering, or simply for pleasure.